The empathic capital of pre-medical students - Sarah D.C. Harvey; Clare L. Stacey; Kelly Rhea MacArthur (Elsevier, 2023)
Literature on the professional and emotional socialization of medical trainees in the US tends to focus on students who have already matriculated into medical school, leaving pre-medical student experiences largely understudied. Specifically, little is known about how these students develop and understand empathy during their pre-medical years. We draw on qualitative interviews with 25 pre-medical students at Midwest University and find that students at this stage possess considerable empathic capital, a resource that they will likely draw on in medical school and beyond. Specifically, pre-medical students understand empathy in cognitive, affective, and action-oriented ways; recall instances of empathic action in their everyday lives; and view empathy as a learned emotional state, shaped in the context of social relationships and the pre-medical curriculum. These understandings of empathy reflect a crucial stage in the development of students' empathy careers (Ruiz-Junco, 2017), as they shift from primary (home and family) to secondary (education, peers) emotional socialization. It behooves medical educators and researchers to understand the empathic capital that medical students "bring to the table" so that empathy training can better incorporate or challenge learners' existing conceptualizations.